The Criminology of White-Collar Crime - Simpson, Sally S. (Springer, 2017)
Over the last few decades, interest in white-collar crime has tended to take a back seat to "street" offenses in terms of theory and research. In response, and reflecting the rising general interest in business and middle/ upper class lawbreaking, The Criminology of White-Collar Crime brings the study of white-collar offending back into the criminology mainstream, analyzing why members of higher social strata resort to criminal activity and offering psychosocial, life course, methodological, and prevention perspectives. Leading scholars expand on the pioneering work of Edwin Sutherland, delving into the variables, situations, and cultural contexts that differentiate white-collar crime from more traditional criminal areas as well as into those that coincide with them.